The Role of Parents in Motivating Dance Art Talent in Early Childhood - Oktira, Yona Syaida; S, Neviyarni; Afdal, Afdal (The Future of Education Journal, 2025)
The role of parents is crucial in developing talent and creativity in the field of dance art among early childhood children. Through active parental involvement in providing motivation, appreciation, a supportive environment, and collaboration with Minangkabau dance studios, parents can facilitate the growth of children’s motor, emotional, and cognitive creativity. This study aims to analyze the role of parents in consistently motivating and fully supporting the talents, interests, and creativity of early childhood children in dance art. This study employs a descriptive qualitative methodology, focusing on parents’ experiences in fully supporting their children’s talents, interests, and creativity in dance art by encouraging and facilitating the development of their children’s dance skills. Data collection techniques involved data triangulation, including observation, interviews, and documentation. Through observation, the researcher monitored the Satampang Baniah dance studio in the Kuranji area and PAUD Tunas Bangsa. Subsequently, in-depth interviews were conducted with parents and dance instructors, and documentation was collected of early childhood children participating in dance performances at an event. The results of this study indicate that parents play a very important role in developing and motivating children’s talents, interests, and creativity in dance art through emotional support, the provision of facilities, and active parental involvement in children’s activities at dance studios, schools, and outside school settings. Parents who provide opportunities for children to remain active and enthusiastic about developing creativity, interests, and talents, as well as space for children to explore dance art, also motivate and encourage children to improve their dance skills and support their social and emotional development. This study further offers recommendations for parents and Minangkabau dance studios to give greater attention to the importance of parental roles in supporting dance art talents in early childhood.